Quality of working life of administrative staff in education at one federal university in Minas Gerais (Research, Society and Development, 2020)
Considering the well-being of workers as a fundamental element for the achievement of organizational interests, in the 1970s the term quality of life at work emerged, initially associated with private companies, but having already reached the public sector. However, for such programs to be effective, it is necessary to investigate the needs of workers. The aim this of this study was to evaluate the technical-administrative in education´s perception about QWL in a federal higher education institution located in the region of Vale do Jequitinhonha, in Minas Gerais. Categories and limits were used to classify QWL in the light of each questionnaire item, and quartiles analysis was used to determine the most critical items. Negative aspects were verified in the eight dimensions analyzed, with emphasis on fair and adequate compensation, working conditions and career opportunities. On the other hand, most respondents highlighted the social relevance and importance of work, considering the geographical location of the University, in one of the most socioeconomic vulnerability of the state. It is concluded that although many critical aspects were detected in the study, some aspects do not depend on the institution for its implementation, especially with regard to salary issues, however, the implementation of still incipient quality of life programs could contribute to mitigate some of people's dissatisfactions and frustrations.